Association between Swallowing-Related Questionnaire Responses and Pathological Signs on Videofluoroscopy in Children - Jana Jančíková; Denisa Bezděková; Petra Urbanová; Lucie Dohnalová; Petr Jabandžiev; Miroslav Tedla; Žofia Frajková; Jiří Jarkovský; Milan Urík (MDPI AG, 2021)
The aim of this study was to identify relationships in children between responses to specific questions of interest in a clinical questionnaire concerning swallowing-related difficulties and pathological signs on a videofluoroscopic swallowing study (VFSS). A prospective data analysis was made of children evaluated with swallowing disorder between January 2018 and April 2021 at a tertiary care centre. Each child enrolled in the study underwent a subjective evaluation (targeted questions) and instrumental examination (VFSS). In total, 51 children suffering from swallowing problems (32 with a neurological disorder and 19 without neurological disorder) were included into the study. Our results showed there was a correlation between the occurrence of specific symptoms (wet voice, wet breathing, recurrent respiratory infections, chronic mucus) and other pathological signs on a VFSS (laryngeal penetration, residua, nasal regurgitation). The evaluation of these specific questions is a reliable and useful method for the management of dysphagia in neonates and infants. It can help us in selecting those patients for which it is appropriate to perform a VFSS.